1995
DOI: 10.1007/bf01973755
|View full text |Cite
|
Sign up to set email alerts
|

Germline transmission of exogenous genes in chickens using helper-free ecotropic avian leukosis virus-based vectors

Abstract: We have used vectors derived from avian leukosis viruses to transduce exogenous genes into early somatic stem cells of chicken embryos. The ecotropic helper cell line, Isolde, was used to generate stocks of NL-B vector carrying the Neo(r) selectable marker and the Escherichia coli lacZ gene. Microinjection of the NL-B vector directly beneath unincubated chicken embryo blastoderms resulted in infection of germline stem cells. One of the 16 male birds hatched (6.25%) from the injected embryos contained vector DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Efforts have mainly involved either the injection of retroviral vectors into embryos at the blastodermal stage (1,7,8,24,26,32,35,36,42,43) or the microinjection of DNA into fertilized eggs at the single-cell stage (21, 39). Recently, lentiviral vectors were also used to generate transgenic chickens (3, 23).…”
mentioning
confidence: 99%
“…Efforts have mainly involved either the injection of retroviral vectors into embryos at the blastodermal stage (1,7,8,24,26,32,35,36,42,43) or the microinjection of DNA into fertilized eggs at the single-cell stage (21, 39). Recently, lentiviral vectors were also used to generate transgenic chickens (3, 23).…”
mentioning
confidence: 99%
“…However, the previous investigators (Vick et al, 1993) never demonstrated beta-galactosidase expression in the offspring. Transgenic chickens carrying the lacZ gene were also produced using a replication-defective avian leukosis based retroviral vector (Thoraval et al, 1995). Unfortunately, beta-galactosidase expression was only noted in cultures of embryonic fibroblasts from G2 progeny, and expression was not reported in the entire embryo.…”
Section: Retroviral Historical Perspectivementioning
confidence: 99%
“…The generation of transgenic chickens has been reported by several groups [49][50][51][52][53][54][55][56][57][58][59]. In the 1980s, bird replication-competent retroviral (RCR) vectors were developed and used for the generation of transgenic chickens [49,50].Although the viral vectors could be amplified in infected cells, the germ-line transmission efficiency was as low as 10%.…”
Section: Transgenic Birds For the Production Of Recombinant Proteins mentioning
confidence: 99%